Living and moving museums: where practice occurs - Ramón, (Comparative Cultural Studies: European and Latin American Perspectives, 2025)
Today, the phenomenon of the indiscriminate display of museum objects, often taken from colonized nations, and the lack of recognition of the cultural and identity value of many pieces are issues that need to be addressed, especially in these times when there is so much talk about respect for otherness and human rights. This is gaining momentum in nations that are taking significant steps with projects to return pieces exhibited for years in Western museums, looted during the period of colonization. However, along with the returns, a change of mentality is needed. It is not enough to restore, but rather to acknowledge what "other" cultures truly symbolize with their ancestry and traditional practices, since not everyone conceives in the same way what has been called a living museum, a term appropriated by many Third World nations. A living museum requires the mysterious aura that only the cultural host can create, free from the Manichaeism and aesthetic constraints often promoted by various hegemonic circles of artistic power. It is necessary to build bridges with otherness to achieve the true miracle of existence.